India`s north-east : identity movements, state, and civil society - Misra, Udayon (OUP)
In many senses, India's Northeast has been an enigma to the rest of the country. Beginning with the earliest challenge of the nation-building process in India, this highly diverse and multicultural region has, through its multiple identity movements and militant separatism, thrown up several major issues which have resulted in re-drawing the parameters of the Indian nation-state and helped to re-define the idea of nationalism itself. This selection of essays/commentaries, written over some three decades, analyze the complex processes of the nation-state's engagement with the demands for autonomy/independence raised by the small nationalities of the northeastern region but also focuses on the contradictions and new equations that have been emerging both within these movements and in the State's response to them. The factors behind the rise of ethnic nationalist assertions, the role of civil society, the rise of exclusivist politics and the question of citizens' rights are other issues that figure prominently in the discussions.
Keywords: Politics and Government